The Role of Antenatal Care in Preparing Mothers for Exclusive Breastfeeding - Adisty Dwi Treasa (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Antenatal Care (ANC) is a health service provided to mothers during pregnancy to monitor the health of the mother and fetus and prepare them for childbirth and the postpartum period . One important aspect that needs to be prepared during pregnancy is exclusive breastfeeding . The success of exclusive breastfeeding is influenced by the mother's physical and psychological readiness , which can be achieved through quality ANC services . This study aims to determine the role of antenatal care in preparing mothers for exclusive breastfeeding . The research method used was quantitative with an analytical design and a cross-sectional approach . The study sample consisted of mothers with infants aged 6–12 months at health care facility X. Data were collected using a questionnaire and analyzed using the Chi- Square test . The results showed that antenatal care plays a significant role in preparing mothers for exclusive breastfeeding (p < 0.05). The conclusion of this study is that mothers who receive standard ANC are better prepared to provide exclusive breastfeeding .